Treating Severe Knee Osteoarthritis with Combination of Intra-Osseous and Intra-Articular Infiltrations of Platelet-Rich Plasma: An Observational Study. (April 2019) - Sánchez, Mikel; Delgado, Diego; Pompei, Orlando; Pérez, Juan Carlos; Sánchez, Pello; Garate, Ane; Bilbao, Ane Miren; Fiz, Nicolás; Padilla, Sabino
Objective: Assessing the therapeutic effects of a combination of intra-articular and intra-osseous infiltrations of platelet-rich plasma (PRP) to treat severe knee osteoarthritis (KOA) using intra-articular injections of PRP as the control group. Design: In this observational study, 60 patients suffering from severe KOA were treated with intra-articular infiltrations of PRP (IA group) or with a combination of intra-osseous and intra-articular infiltrations of PRP (IO group). Both groups were matched for sex, age, body mass index, and radiographic severity (III and IV degree according to Ahlbäck scale). Clinical outcome was evaluated at 2, 6, and 12 months, using the Knee injury and Osteoarthritis Outcome Score (KOOS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaires. Results: At 2, 6 and 12 months after treatment, IO group had a significant improvement in all KOOS and WOMAC subscales ( P < 0.05). On the contrary, patients of the IA group did not improve in any of the scores. Sixteen out of 30 IO group patients showed minimal clinically important improvement (MCII) whereas 8 out of 30 IA group patients showed this response at 6 months (26.7%; 95% CI −0.4 to 49.9; P = 0.037). At 12 months, 14 patients of IO group and 5 patients of the IA group showed MCII (30%; 95% CI 4.3 to 51.9; P = 0.013). No differences between groups were observed at 2 months. Conclusions: PRP intra-articular injections in severe KOA were not effective and did not provide any benefit. Combination of intra-articular and intra-osseous infiltrations of PRP was not clinically superior at 2 months, but it showed superior clinical outcomes at 6 and 12 months when compared with intra-articular injections of PRP.